The Ethical Environment of Tax Professionals: Partner and Non-Partner Perceptions and Experiences - Bobek, Donna D. (Journal of business ethics, 2010)
This article examines perceptions of tax partners and non-partner tax practitioners regarding their CPA firms’ ethical environment, as well as experiences with ethical dilemmas. Prior research emphasizes the importance of executive leadership in creating an ethical climate (e.g., Weaver et al., Acad Manage Rev 42(1):41–57, 1999; Trevino et al., Hum Relat 56(1):5–37, 2003; Schminke et al., Organ Dyn 36(2):171–186, 2007). Thus, it is important to consider whether firm partners and other employees have congruent perceptions and experiences. Based on the responses of 144 tax practitioners employed at CPA firms, the results show that tax partners rate the ethical environment of their firms as stronger than non-partner tax practitioners, particularly among those who describe a self-identified ethical dilemma. Tax partners also report having encountered more of the common examples of researcher-provided ethical dilemmas than non-partner tax practitioners, although non-partners perceive that certain ethical dilemmas occur at a higher rate than partners do. Overall, this study provides evidence of a disconnect between tax partners and non-partner tax practitioners with respect to perceptions of organizational ethics. Suggestions for potential remedies are offered.